Advances in agronomy. - Sparks, Donald L., 1953- (Advances in Agronomy., 1997)
Written by international authorities in agronomy, Volume 60 contains five comprehensive reviews covering key contemporary topics on plant and soil sciences. As always, the topics are varied and exemplary of the array of subject matter covered by this long-running serial. This volume contains a state-of-the-art review on adapting plants to salinity, the effects of no-tillage cropping systems on soil microbiological relationships, sustainability of agroecosystems in semiarid regions, ethics in agronomic research, and nutrient cycling information. With this latest volume, Advances in Agronomy continues to be recognized as a leading reference and as a first-rate source of the latest research in agronomy, crop science, and soil science. Key Features * Nutrient cycling, transformation and flows * Adaptation of plants to salinity * Practical ethics in agronomic research * The influence of no-till cropping systems on microbial relationships * The sustainability of agroecosystems in semiarid regions.